Internalisasi Nilai-Nilai Karakter Melalui Kajian Kitab Safinah An-Najah pada Remaja Dusun Bedilan Margokaton Seyegan Sleman - Hidayatullah Hidayatullah (Institut Agama Islam Hidayatullah Batam, 2025)
This study examines the internalization of adolescent character values ​​through a study of religious books.Safinah an-Najahin Dusun Bedilan. Qualitative case study method was used with interview, observation, and documentation techniques. The results of this study explain that values ​​such as honesty, responsibility, discipline, and social concern are instilled through the methodthe bandongcontextually. Success is influenced by communicative ustadz, support from community leaders, and the role of parents. The obstacles include low interest among teenagers and difficulty in understanding the language of the book. Despite the obstacles, this study has a positive impact on the formation of adolescent character, both in worship and social life. The process is carried out continuously and interactively, making the yellow book an effective medium for developing Islamic character for the young generation in rural areas.